Evaluation of a special needs dental workshop for health professionals and students in Trinidad and Tobago - Balkaran Ramaa; Perry Maureen; Maharaj Anushka; Rajhbeharrysingh Amrita; Virtanen Jorma I. (Switzerland, 2022)
Aims: This study aimed to evaluate a special needs dental workshop for dentists, allied dental health professionals and students in Trinidad and Tobago.
Methods: This feedback study conducted in 2019–2020, included two surveys, one at the time of the workshop and a second survey one year after it. The first survey utilized an anonymous self-administered questionnaire enquiring about the reason for attendance, profession/education, demographics, and difficulties faced in treating patients with special needs. The follow-up study used an online survey tool assessing the workshop and queried comments/suggestions. The Chi-square test served for statistical analysis.
Results: Of the 176 attendees 131 participated (response: 74.4%). The majority (81.5%) were females. Most attendees were dental students (50.3%) or dentists (38.9%). Knowledge acquisition (73.1%) and professional development (14.2%) were the main motives for attendance while communication (31.8%) and non-compliance (34.5%) were the main problems faced in treating patients with special needs. The follow-up evaluation (post-workshop) (response: 72.5%) showed that most participants (90.5%) assessed the workshop as positive; 80% reported an increase in their knowledge and 64.2% perceived a need for further education.
Conclusion: These findings suggest a considerable demand for special needs dental services and continuing education and show that workshops can actively affect patient care.